2019
DOI: 10.3390/vetsci6040080
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Bovine Granuloma Formation In Vitro upon Infection with Mycobacterium Avium Subspecies Paratuberculosis

Abstract: Mycobacterium avium subspecies paratuberculosis (Map) causes chronic granulomatous disease in cattle and ruminant livestock, causing substantial economic losses. Current vaccines delay clinical signs but cannot train the immune system to fully eradicate latent Map. During latency, Map uses host defenses, cage-like macrophage clusters called granuloma, as incubators for months or years. We used an in vitro model to investigate the early coordination of macrophages into granuloma upon Map infection over ten days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 81 publications
0
8
1
Order By: Relevance
“…Despite the fact that TNF-α, IL-1β, IL-6 and IFN-γ cytokines have been implicated in the in vitro activation of Th1 immune response, the destruction of Map and the development of characteristic granulomas [ 58 61 ], the current study found no significant influence of vaccination or infection over the transcription of these cytokines by CaMØs, presumably due to the high individual variability. Previous in vitro studies have shown the effect of IFN-γ on the acidification and maturation of phagosomes in MDMs that reduce Mycobacterium avium subsp.…”
Section: Discussioncontrasting
confidence: 70%
“…Despite the fact that TNF-α, IL-1β, IL-6 and IFN-γ cytokines have been implicated in the in vitro activation of Th1 immune response, the destruction of Map and the development of characteristic granulomas [ 58 61 ], the current study found no significant influence of vaccination or infection over the transcription of these cytokines by CaMØs, presumably due to the high individual variability. Previous in vitro studies have shown the effect of IFN-γ on the acidification and maturation of phagosomes in MDMs that reduce Mycobacterium avium subsp.…”
Section: Discussioncontrasting
confidence: 70%
“…This poses an additional problem in terms of developing novel treatments and rapid diagnostic tests, as the pathogens effectively have a mammalian cell shield preventing the drug or the probe accessing its target. This becomes a greater issue as the infection progresses, as infected macrophages eventually differentiate into epithelioid cells, which aggregate to form granulomas to suppress bacterial growth (Martcheva et al ., 2015; Rice et al ., 2019). Within the granuloma, MAP enters a dormant state and can gradually reactivate in later stages of infection, resulting in intermittent shedding of MAP in mid-stage disease (Martcheva et al ., 2015; Rice et al ., 2019; Garvey, 2020).…”
Section: Johne's Diseasementioning
confidence: 99%
“…MAP bacteria that travel across the intestinal epithelium are phagocytosed by macrophages via complement receptors. Infected macrophages form granulomas and become a latent infection or active disease ( Birkness et al, 2007 ; Rice et al, 2019 ).…”
Section: Bacterial Species Associated With Human Inflammatory Bowel D...mentioning
confidence: 99%